Kinerja Pelayanan Sarana Umum di Kawasan Permukiman Terpadu Panakukang Mas Kota Makassar Berdasarkan Pendapat Masyarakat Pengguna - Bandaso, Tyoer R. A. (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2015)
With the position of the Panakukang Mas region as a center integrated settlement services, can create a basic urban problems that limited the availability of public facilities and qualified in accordance with the dynamic needs of the community with the implementation of good governance of public service. Research using quantitative methods with descriptive analysis of the availability of public facilities and public satisfaction index scoring analysis of the public services facilities. The technique of collecting data through observation and questionnaires to a unified settlement Panakukang Mas area, and a review of documents that are expected to provide an overview of service performance and the provision of public facilities in Panakukang Mas. The results show the performance of public services facilities integrated residential areas Panakukang Mas region by the user community or the average of the respondents are in the public satisfaction index score service performance from 62.51 to 81.25 or better. The quality of public infrastructure services in an integrated residential Panakukang Mas increased with good performance and focus on the location and distance to public facilities. Performance measurement showed improvement in the quality of running public services based on the needs of the provision of public infrastructure and public service standards.